The deep structure of the Trans-European Suture Zone (based on seismic survey and GSR data) and some insights in to its development - Gintov, O.B.; Tsvetkova, T.О.; Bugaenko, I.V.; Zayats, L.N.; Murovska, G.V. (Geofizicheskiy Zhurnal, 2023)
Deep crust and mantle structure of the Trans-European Suture Zone (TESZ) is considered on the basis of geological and geophysical investigations in the Baltic Sea-Black Sea section. The crustal structure of TESZ was studied on the basis of wide-angle depth seismic sounding (WDS), which was performed by international scientific teams with the participation of the Institute of Geophysics of NAS of Ukraine (IGF NASU). TESZ mantle structure was studied down to a depth of 800 km by the 3D P-velocity model of the Eurasian mantle according to the Taylor approximation method developed in the Institute of Geophysics of NASU. It is concluded that the deep crustal and mantle structure of the zone is a result of the simultaneous action of plate- and plum tectonic processes. TESZ was formed on two major collision alstages: in the late Ordovician — early Silurianas a result of the accession of the Avalonia microcontinent to the East European Platform (EEP), and in the late Carboniferous – early Permian with the accession of the European Hercynian (Varisian) terranes to EEP. The TESZ crustal structure is a trough of 150 (sometimes up to 200) km wide and several to 21 km deep, built by the allochthonous complex of paleozoids that underwent Caledonian and Hercynian orogens beyond the trough. Mantle structure of the TESZ, according to seismic tomographic studies, is of dual nature: on the one hand, the zone is traced subvertically to a depth of 700 km, on the other, within the zone there are everywhere inclined layers — slips to the depth of 350—600 km, that is the traces of subduction processes, which precededorac companied TESZ formation. Both structural features overlapeachother, which complicates paleotectonic and geohistorical analysis of TESZ formation. TESZ sinking to greater depths in the mantle can be explained by its increased permeability for advection of ultra-deep mantle fluids, established hereborogensic tomographic and paleomagnetic methods. Several variants of TESZ formation are assumed — A- or B-subduction during north eastern plate thrusting under the south western one in all variants.